Foundations of Health Informatics Engineering and Systems First International Symposium, FHIES 2011, Johannesburg, South Africa, August 29-30, 2011. Revised Selected Papers - Liu, Zhiming; Wassyng, Alan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed proceedings of the First International Symposium on Foundations of Health Informatics Engineering and Systems, FHIES 2011, held in Johannesburg, South Africa, in August 2011. The 14 revised full papers presented in this volume were carefully reviewed and selected from 23 submissions. The papers are grouped in topical sections on protocols for diagnosis and clinical trials; modeling workflows; model checking workflows and control systems; interoperability; formal modeling of organs and devices; and safety, security, and privacy of medical records.
Protocols for diagnosis and clinical trials -- modeling workflows -- model checking workflows and control systems -- interoperability -- formal modeling of organs and devices -- safety, security, and privacy of medical records.
Keywords: Computer science; Computer Science; Computer Science, general; Computer Science, general; Computer Science, general; Computer Science, general; Computer Science, general; Computer Science, general